ANALISIS TINGKAT KEPUASAN PASIEN TERHADAP MUTU PELAYANAN RUMAH SAKIT BERDASARKAN METODE SERVICE QUALITY (SERVQUAL) - Beny Irawan; Erwin Daniel Sitanggang (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2020)
Measuring the level of patient satisfaction at the hospital is done to measure the performance of the services provided. In measuring the level of satisfaction in the March 2020 period at the GrandMed hospital, it involved 98 inpatients as a sample of a population of 129 patients. The data collection techniques used were non-probability sampling with purposive random sampling and purposive random sampling. By using the servqual method, as a whole, it is by the expectation with a satisfaction level gap score of 0.10 with a patient satisfaction level of 53.06%. In the dimension of the gap score is 0.22 for the Assurance variable, 0.16 for the Physical Evidence variable, 0.12 for the Empathy variable, 0.08 for the Reliability variable, and -0.08 for the Responsiveness variable. To improve service quality, it is necessary to improve the performance of the attributes of the statement, especially those in the reliability dimension.